Economic consequences of the devolution package and an evaluation of decentralisation - Hewavitharana, Buddhadasa (Colombo : Sinhala Weera Vidahana, 1997)
With reference to Sri Lanka.
Includes bibliographical references (p. 213-217).
Keywords: Decentralization in government -- Sri Lanka; Central-local government relations -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-